Factors that influence experiential value of timeshare owners toward timeshare purchasing in Malaysia - Za’ba, Airin Niza; Kumar M., Dileep (International Foundation for Research & Development, 2015)
This study was conducted to investigate factors that influencing experiential value of time share owners in purchasing timeshare in Malaysia.The research framework was constructed based on the extensive literature review to establish the hypothesis.The researcher used questionnaire and the respondents is among the timeshare owners from Malaysia.Quantitative methods were applied in the research for validity. The analysis of the findings of this research reveals that whether involvement of infrastructure, security, risk, cost and price would have bring significant experiential value to the timeshare owners.